Suo Quan Wan Protects Mouse From Early Diabetic Bladder Dysfunction by Mediating Motor Protein Myosin Va and Transporter Protein SLC17A9 - Wang, Jing; Lian, Da-wei; Yang, Xu-feng; Xu, Yi-fei; Chen, Fang-jun; Lin, Wei-jun; Wang, Rui; Tang, Li-yao; Ren, Wen-kang; Fu, Li-jun; Huang, Ping; Cao, Hong-ying (Frontiers in Pharmacology, 2019)
OBJECTIVE: To investigate the effects of Suo Quan Wan (SQW), a traditional Chinese herbal formula, on the overactive bladder (OAB) of type 2 diabetes mellitus (T2DM) mouse models, particularly on its function of mediating the gene and protein expression levels of myosin Va and SLC17A9. MATERIALS AND METHODS: After 4 weeks high-fat diet (HFD) feeding, C57BL/6J mice were injected with streptozotocin (100 mg/kg) for four times. After 3 weeks, the diabetic mice were treated with SQW for another 3 weeks. Voided stain on paper assay, fasting blood glucose (FBG) test, and oral glucose tolerance test (OGTT) were conducted. Urodynamic test, tension test (α,β-methylene ATP, electrical-field stimulation (EFS), KCl, and carbachol) and histomorphometry were also performed. Western blot analysis and qPCR assays were used to quantify the expression levels of myosin Va and SLC17A9. RESULTS: The diabetic mice exhibited decreased weight but increased water intake, urine production, FBG, and OGTT. No significant changes were observed after 3 weeks SQW treatment. Urodynamic test indicated that the non-voiding contraction (NVC) frequency, maximum bladder capacity (MBC), residual volume (RV), and bladder compliance (BC) were remarkably increased in the diabetic mice, whereas the voided efficiency (VE) was decreased as a feature of overactivity. Compared with the model mice, SQW treatment significantly improved urodynamic urination with decreased NVC, MBC, RV, and BC, and increased VE. Histomorphometry results showed that the bladder wall of the diabetic mice thickened, and SQW effectively attenuated the pathological alterations. The contract responses of bladder strips to all stimulators were higher in the DSM strips of diabetic mice, whereas SQW treatment markedly decreased the contraction response for all stimuli. Moreover, the protein and gene expression levels of myosin Va and SLC17A9 were up-regulated in the bladders of diabetic mice, but SQW treatment restored such alterations. CONCLUSIONS: T2DM mice exhibited the early phase of diabetic bladder dysfunction (DBD) characterized by OAB and bladder dysfunction. SQW can improve the bladder storage and micturition of DBD mice by mediating the protein and gene expression levels of myosin Va and SLC17A9 in the bladder, instead of improving the blood glucose level.